Diseño de circuitos analógicos basados en amplificadores operacionales usando algoritmos genéticos con función de aptitud difusa - Sanabria Muñoz, Federico Andres; Hostos Orjuela, Hector Leonardo; Melgarejo Rey, Miguel Alberto (Ingeniería, 2008)
This paper presents a genetic algorithm approach to the design of analog circuits consisting of operational amplifiers. The input of the algorithm is the transfer function of the required system. The fitness function of the genetic algorithm is implemented by means of a fuzzy inference system. A summary of the methodology used in the design is included and results with a specific circuit topology for multiple transfer functions are reported.